PENGARUH GAYA KEPEMIMPINAN DAN KOMITMEN TERHADAP PERILAKU KEANGGOTAAN (OCB) PADA PEGAWAI DI YAYASAN MIMA NURUL HUDA GONDANGREJO CAKRU KENCONG KABUPATEN JEMBER - A. Kharisul Anam; Hadi Sunaryo (UNIVERSITAS ISLAM MALANG, 2017)
ABSTRACT This study aims to analyze and influence the influence of leadership style and commitment to the behavior of membership (organizational citizenship behavior) on the employees of Yayasan Mima Nurul Huda Gondang Rejo Cakru Kencong Jember District. Data analysis method used is multiple linear regression analysis, Normality Test, f test and t test. Based on the results of data analysis, the regression equation in the can is as follows:The result of t test, there is no positive or significant influence of leadership style on membership behavior, and there is significant positive influence of organizational commitment to teacher membership behavior at Yayasan Mima Nurul Huda Gondang Rejo Cakru Kencong Jember Regency. Results simultaneously with F test show that all leadership style and commitment variables significantly influence OCB. Keywords: Leadership Style, Commitment, and Membership Behavior